Effectiveness of E - Module Implementation Using STEM Project-Based Learning on Statistics Materials - Rosita Dwi Ferdiani Ferdiani (Universitas Kanjuruhan Malang, 2022)
The purpose of this study was to determine the effectiveness of implementing e-modules based on STEM Project-based learning on statistical material. This research is qualitative and quantitative. The types of data in this study are qualitative and quantitative data. Qualitative data is generated from the input and suggestions of teachers (learning experts) and respondents. Quantitative data in the form of scores from the questionnaire and test results done by students. The instruments used in this study were e-modules based on STEM Project-Based Learning, tests, and questionnaires. The subjects of this study were students of class VIII SMP Al Inayah. Based on the results of the study, it was found that: 1). Assessment of effectiveness based on the results of test scores obtained by students during limited field trials (small groups) showed that students' completeness scores were 80% reaching a score of 75 or above the KKM (Minimum Completeness Criteria). This percentage is located on a criterion scale of 80% < ð‘‹Ì… â‰¤ 100%, so the test results show that the e-module developed is in the